Behavioral manifestations and underlying mechanisms of amphetamine in constructing animal models of mania: a comprehensive review - Deng, Zi-Qi; Si, Xiao-Chen; Song, Jia-Bin; Li, Jin-Yao; Sun, Lu; Dang, Xue; Zhao, Min; Feng, Yan-Chen; Liu, Fei-Xiang (Frontiers in Neuroscience, 2025)
Mania is a mind disorder with heightened emotions, etc. Amphetamine (AMPH), a drug with central nervous system excitatory effects, can disrupt neurotransmitter release and metabolism, causing mania. AMPH-induced animal models of mania show increased risk and reward-seeking behaviors and excessive locomotion like mania patients, verifiable by tests like Elevated Plus Maze (EPM). It also impacts neurotransmitter balance in different brain regions, aligning with the imbalance in mania patients. Multiple signaling pathways including extracellular regulated protein kinases and others are involved, and their altered activities link to mania symptoms. In the AMPH-induced mania model, regions like the frontal cortex have increased oxidative stress and inflammatory response. Moreover, AMPH changes neurotrophin levels, potentially causing neuronal damage and cognitive impairment. In summary, the AMPH-induced mania animal model is crucial for studying mania’s pathogenesis. However, further in-depth studies on neurotransmitter regulation, signaling pathway intervention, and neurotrophic factors are needed to develop more effective and personalized treatment plans.